Gas-to-particle partitioning of atmospheric amines observed at a mountain site in southern China. (December 2018) - Liu, Fengxian; Bi, Xinhui; Zhang, Guohua; Lian, Xiufeng; Fu, Yuzhen; Yang, Yuxiang; Lin, Qinhao; Jiang, Feng; Wang, Xinming; Peng, Ping'an; Sheng, Guoying
Abstract: Amines play an important role in the formation and transformation of atmospheric aerosols. Gaseous phase and PM2.5 samples were collected simultaneously at Nanling Mountains, southern China during autumn 2016 and summer 2017. The site is strongly affected by long distance transport from marine and continental air masses. Five amines, methylamine (MA), dimethylamine (DMA), diethylamine (DEA), dibutylamine (DBA) and morpholine (MOR), were detected by gas chromatography-mass spectrometry (GC-MS) after derivatization. The backward trajectory analyses suggested that different origins of air masses led to seasonal variation of amines. In gaseous phase samples, the average concentrations of total measured amines (Ʃamines) were 193.4 ± 111.7 ng m −3 in autumn 2016 and 307.5 ± 196.7 ng m −3 in summer 2017. In PM2.5 samples, the average concentrations of Ʃamines were 12.4 ± 10.8 ng m −3 in autumn 2016 and 20.7 ± 11.0 ng m −3 in summer 2017. MA and DMA were the dominant amines, together contributing approximately 70% to gaseous amines and 80% to particulate amines. A strong linear relationship was found between Ʃamines and NO3 − in PM2.5, implying that amines might mainly exist in the form of aminium nitrate. Ammonium (NH4 + ) was found mostly likely in the form of ammonia sulfate. Approximately 7.4% of the gaseous total amines partitioned to PM2.5 . A good linear relationship between the fraction of total atmospheric concentration sorbed by PM2.5 ( Φ) and the concentrations of O3 was found, suggesting that O3 likely played an important factor in the gas-to-particle partitioning of amines. Additionally, under high relative humidity circumstances (92% ± 7.0%), direct dissolution was a crucial step for gaseous amines partitioning into particles. The ratios of amines-C to water-soluble organic carbon (WSOC) and amines-N to water-soluble organic nitrogen (WSON) were 0.21% and 1.57% in autumn 2016 and 0.54% and 2.08% in summer 2017, respectively. The results of this study provide essential information on the formation mechanism of particulate amines. Highlights: Gaseous and particulate amines were detected simultaneously at a remote mountain site in southern China. Amines were mostly likely in the form of aminium nitrate. Approximately 7.4% of the total gaseous amines partitioned into the particulate phase. Direct dissolution was a crucial step for gas-to-particle partitioning under high relative humidity circumstances.